Anti-inflammatory activity of neral and geranial isolated from fruits of Litsea cubeba Lour. (December 2015) - Liao, Pei-Chun; Yang, Tsung-Shi; Chou, Ju-Ching; Chen, Jie; Lee, Shu-Ching; Kuo, Yueh-Hsiung; Ho, Chen-Lung; Chao, Louis Kuo-Ping
Highlights: The first study on the anti-inflammatory cellular molecular mechanisms of the two isomers of citral, neral and geranial. Neral and geranial were also found to have the ability to inhibit inflammasomes. Neral and geranial induced different intracellular molecular responses and expression of ROS in macrophages. Abstract: Fruits of Litsea cubeba are a spicy condiment, frequently used in the aboriginal cuisine of Taiwan. Earlier studies found that the fruit contains a high amount of citral, which is also a commonly used food additive ingredient. In this study, we separated citral into neral and geranial in pure forms. At 66 µM dose, neral showed greater inhibition of TNF-α and IL-6 secretion of macrophages after stimulation by LPS than did geranial; with 81.4 and 58.2% vs. 63.6 and 46.8%, respectively. Furthermore, compared with geranial, neral demonstrated better efficacy in inhibiting expression of the inflammatory mediators pro-IL-1β, iNOS, COX-2 and NLRP-3. Both neral and geranial exhibited significant and similar inhibition of NLRP-3 inflammasome-mediated IL-1β secretion; however, the two compounds had different inhibitory effects on the phosphorylation of ERK1/2, JNK1/3, p38 and IκB. This is the first study reporting the differences between the anti-inflammatory cellular molecular mechanisms of the two isomers of citral, neral and geranial, which may be regarded as components of functional food ingredients.